A extinção das ordens religiosas e os conventos do Porto: transformação, ruptura e continuidade - Maria José Lopes Casanova (2015)
Characterized by the implantation of convents and monasteries that settled in the city and its outskirts between the thirteenth and eighteenth centuries, Porto, as an episcopalian town of bourgeois vocation, maintains visible architectural and urbanistic consequences of the extinction of religious orders in urban countenance. In cities throughout Portugal, as in all Catholic Europe, after the extinction of religious orders, the architectural patrimony of confiscated convents will be appropriated and used by various organizations of the new liberal regime. In parallel, the disintegration of fences will facilitate designs projected for the development of urban structure(s), allowing the construction of layouts that value the straight line, circulation and hygiene or the concretization of ideals of development and progress. Integrated in 30th May 1834, by decree, in the National Assets, they will also be sold in public auction, receiving private institutions and manufacturing facilities or, when demolished and divided, will give origin to new residential sets. Stemming from the analysis of maps of conventual networks of the city of Porto, and drawing ties of the origins of religious orders (with spiritual variants of several branches), connections will be established between objectives, stages and epochs of establishment of religious orders with the evolution of urban spaces, integrating its implantation in the characteristics of topography and urban morphology. Through this examination it is possible to give evidence to possible directions of articulation between the different houses and simultaneously confirm the existence of convents as architectural facts of exception, with major significance in the construction of urban space and the image of the city. Moreover, we investigated the transformation of the city of Porto in spaces once occupied by convents, and/or in its context, by interpreting the meaning of urban environment in different periods - before and after extinction. Going further on the analysis of propositions and partial projects that had once been made for the city in order to analyse how the new condition of these unoccupied religious structures is manifested in the evolution of the city throughout the nineteenth century. Whether through the integration of different projected actions for the conventual set of buildings in the city centre within walls, whether through the confrontation between projects of different time periods for sets of buildings situated in strategic parts of town, we draw evidence of different approaches of thinking the city from emblematic operations, confirming the transformation of these conventual places as synthetic history of new themes and programs of nineteenth century city, as well as of the emerging urban restructuring. Resorting to the juxtaposition of temporal layers or "multiple times" that, by making the convergence of spatial dynamics emerge, as representative of distinct worldviews in the same place, allows us to confirm them as strategic places in the urban tissue and morphology. This global view allows us, not only to reflect on how convents contributed to the construction of the contemporary city, by demonstrating how the city intended to, and interacted with convents, namely through its locations and characteristics of the site, but also how convents (by its value of position), interacted with the city, enhancing new articulations and/or orienting new developments. By crossing the problematics of the site when faced with different practices of production of the urban space, this research gives evidence of the capacity of these structures to reconnect in different systems of organization. Furthermore, by exposing the different religious orders that constituted the city as detainers of distinct matrix-like qualities, this research generates new reflections on the role these structures played / play in the global context of the city, viewed as a complex system of various significant places.